Indirect Fortification of Traditional Nixtamalized Tortillas with Nixtamalized Corn Flours - María Guadalupe Nieves-Hernandez; Brenda Lizbeth Correa-Piña; Oscar Garcia-Chavero; Salomon Lopez-Ramirez; Rosendo Florez-Mejia; Oscar Yael Barrón-García; Elsa Gutierrez-Cortez; Marcela Gaytán-Martínez; Juana Isela Rojas-Molina; Mario E. Rodriguez-Garcia (Foods)
Background: This work focused on the study of the indirect fortification of Mexican tortillas made from nixtamalized masa (NM) with nixtamalized commercial corn flour (NCC-F) fortified with Zn, Fe, vitamins and folic acid. Methods: The chemical proximate values (CPV), ash content, mineral composition by inductively coupled plasma, in vitro protein digestibility (PD), protein digestibility-corrected amino acid score (PDCAAS), the total starch content, the resistant starch (RS) content in nixtamalized corn tortillas (NC-T) and nixtamalized commercial corn flour tortillas (NCCF-T) and the contribution of tortillas prepared with a mixture of NM and NCC-F (75:25 and 50:50, NM:NCC-F) to the recommended dietary intake (RDI) of minerals and vitamins were determined. Results: No significant differences (p < 0.05) were found in CPV and RS content between NCCF-T and NC-T. Ca content was significantly higher (p < 0.05) in NC-T than in NCCF-T, while Fe, K, Zn, folic acid contents, PD and PDCAAS content was higher in NCCF-T compared to NC-T (p < 0.05). The tortillas made with a mixture of NM and NCC-F (50:50) provide 43.07% of the RDI of Ca for Mexican children and adults, while ~45% and >100% of the RDI of Mg for adults and children, respectively, are provided by these tortillas. Similarly, tortillas from the NM:NCC-F mixture (50:50) provide average values of 45, 71 and ~91% of the RDI of Fe, Zn and folic acid, respectively, for all age groups of the Mexican population. Conclusions: NCCF-T contribute significantly to the recommended daily intake (RDI) of micronutrients such as iron, zinc, magnesium and folic acid, while tortillas made from the traditional nixtamalized corn of the Mexican diet have a higher calcium content. Tortillas made from a mixture of NCC-F and traditional NM may be an effective way to address micronutrient deficiencies in the Mexican population.